Value-Based Human Resource Management in Islamic Education: Reconstructing the CLBM Philosophy in Gayo Society - Emy Yusdiana; Amiruddin Siahaan; Mardianto Mardianto (Dirasah International Journal of Islamic Studies, 2026)
Contemporary human resource management in education frequently emphasizes technocratic efficiency and administrative metrics, often marginalizing indigenous ethical frameworks. Within the Gayo community of Aceh, the traditional philosophical values of Cerdik, Lisik, Bidik, and Mersik (CLBM) have historically served as vital moral compasses guiding social conduct, character development, and professional integrity. Despite their cultural significance, the systematic integration of CLBM into modern Islamic educational management remains critically underexplored. This study, therefore, aims to reconstruct the CLBM philosophy as a culturally responsive framework for value-based human resource management in Islamic education. Utilizing a qualitative research design, data were collected through in-depth interviews, direct observations, and document analysis involving customary leaders, educators, and cultural experts in Central Aceh. The findings demonstrate that CLBM functions as a comprehensive ethical system that shapes leadership and professional behavior. Nevertheless, its practical implementation in educational HRM is hindered by rapid modernization, heavy administrative workloads, and a lack of formal institutional integration. Consequently, this study advocates for the strategic reconstruction of CLBM values to align with contemporary educational standards. Embedding these principles into recruitment, continuous professional development, and performance assessment can significantly strengthen teacher professionalism, institutional credibility, and community trust. Ultimately, this research provides a sustainable, culturally grounded paradigm for ethical human resource management in Islamic educational settings.